Asymptotic Behavior of Solutions of Nonlinear Difference Equations with Continuous Argument - Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We establish conditions for the existence and uniqueness of continuous asymptotically periodic solutions of nonlinear difference equations with continuous argument.